UiTM Global News : Engaging the world (Vol.3 / December 2019) - UiTM, Office of International Affairs (Office of International Affairs, 2019)
A quarterly newsletter showcasing UiTM's Internationalisation activities with the motto "Engaging the World." It features the engagement of UiTM with its partners at the global level. The last quarter of the year saw UiTM very active on the international front, making waves in international collaborations and partnerships. For the very first time, UiTM made its physical presence felt in Tanzania, in East Africa, the gateway to Africa. In addition, UiTM's global engagements took us to Bosnia Herzegovina where MOUs were signed with the universities there. We then head on to Fukuoka, Japan to witness UiTM receiving the award for The Most Creative Corporate Video. Congratulations UiTM!